Communicative Language Teaching (CLT) Strategies in Daily Lesson Plans of Oral Communication Teachers and their Alignment to Standards in Curriculum Guide - Bargo, Darwin; Go, Mildred B. (International Journal of Linguistics, Literature and Translation, 2021)
Communicative Language Teaching (CLT) is an approach that has been the subject of many practitioners and researchers in the field of language teaching and applied linguistics in many countries like the Philippines because of the recent changes and educational reforms, including lessons and curriculum innovations. Anchored to the CLT theory, this study used quantitative-qualitative content analysis of the daily lesson plans of the 7 purposively sampled Senior High School (SHS) language teachers teaching Oral Communication in Context (OCC). This aimed to identify the activities by cluster, assess which activities are CLT strategies, and determine their alignment to standards in the curriculum guide. Results revealed that the strategies used as classified through content analysis, and according to type and frequency included task-completion activity, opinion-sharing activity, mechanical practice activity, information-transfer activity, reasoning-gap activity, information-gap activity, communicative activity, information-gathering activity, fluency activity, accuracy activity, meaningful practice activity, and others. A number of strategies matched the CLT principles and features but vary on their respective percentages in each of the four phases, i.e., Activity-Analysis-Abstraction-Application (4As) of the lesson. These CLT strategies were found to be aligned to the Department of Education’s curriculum guide in terms of content standards, performance standards and assessment types. Implications of the findings to language teaching in the Philippines were drawn.